Source of the low‐altitude hiss in the ionosphere. Issue 5 (3rd March 2017) - Chen, Lunjin; Santolík, Ondrej; Hajoš, Mychajlo; Zheng, Liheng; Zhima, Zeren; Heelis, Roderick; Hanzelka, Miroslav; Horne, Richard B.; Parrot, Michel
Abstract: We analyze the propagation properties of low‐altitude hiss emission in the ionosphere observed by DEMETER (Detection of Electromagnetic Emissions Transmitted from Earthquake Regions). There exist two types of low‐altitude hiss: type I emission at high latitude is characterized by vertically downward propagation and broadband spectra, while type II emission at low latitude is featured with equatorward propagation and a narrower frequency band above ∼ f cH+ . Our ray tracing simulation demonstrates that both types of the low‐altitude hiss at different latitude are connected and they originate from plasmaspheric hiss and in part chorus emission. Type I emission represents magnetospheric whistler emission that accesses the ionosphere. Equatorward propagation associated with type II emission is a consequence of wave trapping mechanisms in the ionosphere. Two different wave trapping mechanisms are identified to explain the equatorial propagation of Type II emission; one is associated with the proximity of wave frequency and local proton cyclotron frequency, while the other occurs near the ionospheric density peak. Key Points: The observed characteristics of low‐altitude hiss in the ionosphere are presented Whistler mode in the magnetosphere serves as the source for the low‐altitude hiss in the ionosphere The mechanisms for accessibility to the ionosphere have been identified for explaining the observed features of the low‐altitude hiss